Flood Analysis On The Tailing Dam At Way Linggo, Lampung Province - Lilies Widojoko (Universitas Bandar Lampung, 2011)
Abstract : The Soil Conservation Service (SCS) runoff Curve Number (CN) was developed as an index that represents the combination of a hydrologic soil group and a land use and treatment class.Tailling Dam Way Linggo is located in Lampung Province.Due to the absence of an automatic water level recorder in the project site , another recorder in neighbouring catchment that is Banjaragung, catchment, which is the smallest catchment area in the Way Seputih Sekampung River basin, had to be selected.Calibration of model parameters for Banjaragung catchment to validate the CN method for use at the Tailing location. Reconstitution of two Flood Hydrographs for the 1981 and 1982 events are are sufficient for conclusion that parameters are representing actual hydrological conditions for losses composed in Curve Numbers, Baseflow parameters and unit hydrograph of Soil Conservation Service (SCS) parameters (time lag depending on river length) in Tailling Dam Way Linggo, or in other words, the Curve Number can also be applied in the Tailing Dam catchment.